ANALISIS KARAKTERISTIK ALIRAN MELALUI PENAMPANG PERSEGI PANJANG MENGGUNAKAN MODEL TURBULEN LARGE EDDY SIMULATION (LES) - Barata, La Ode Ahmad; Samhuddin, Samhuddin (Jurnal Rekayasa Mesin, 2024)
Dynamic response, fatigue, and stability issues of a structure are closely related to flow behavior past a bluff body structure. Flow past the free-end rectangular prism is investigated numerically using a Large Eddy Simulation (LES) turbulence model at Re = 22000. The prism model has a constant depth (D) to width (H) ratio D/H = 0.5 for span length variation L (= 10; 7,5; 5,0 and 2,5H). Effects of the free end on the flow characteristics showed that the flow pattern, velocity vector, and fluid forces component are changed. The presence of the free end is closed related to the flow characteristics alteration in the wake, which is presented graphically in this paper. This study suggests the critical aspect ratio of the slender rectangular is 2,5<L/H<5,0 The prism with critical aspect L = 2,5H presented an unusual flow behavior among the test models. The dynamic response of the test model affects the flow pattern in the wake, which is indicated by alteration of the region and intensity of vorticity, velocity vector, hydrodynamic force components, and other local components.